High-temperature-resistant new energy automobile wire harness and preparation method thereof

By synthesizing dendritic mesoporous silicon oxide particles in automotive wiring harness materials and performing surface modification, combined with thermoplastic polyester elastomer TPEE matrix, the problem of insufficient heat resistance and mechanical strength of existing automotive wiring harness materials under high temperature and high stress conditions is solved, and higher heat resistance and mechanical strength is achieved, extending the service life of the wiring harness and reducing maintenance costs.

CN119592019AInactive Publication Date: 2025-03-11HUNAN YILISHENG ELECTRONICS TECH

Patent Information

Application Number
CN202411634096.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing automotive wiring harness materials are difficult to meet the requirements of heat resistance and mechanical strength under high temperature and high stress conditions, resulting in their vulnerability to damage during use and high maintenance costs.

Method used

By synthesizing dendritic mesoporous silicon oxide particles, forming amino groups and grafting phosphorus-containing groups on the surface of the particles, combining thermoplastic polyester elastomer TPEE matrix, modified fillers are prepared to enhance the heat resistance and mechanical strength of the wire harness protective sleeve material.

Benefits of technology

The heat resistance and mechanical strength of the wire harness protective sleeve material is significantly improved, so that it can effectively protect the vehicle wire harness under high temperature and high stress conditions, extend its service life and reduce maintenance costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-temperature-resistant new energy automobile wire harness protective sleeve material. The preparation method comprises the following steps: (1) preparing filler powder; (2) preparing a primary treatment filler; (3) gamma-methacryloyloxy propyl trimethoxy silane and 9, 10-dihydro-9-oxa-10-phosphaphenanthrene-10-methyl propionate 10-oxide are used for treatment, and a modified filling material is obtained; and (4) weighing the vacuum-dried thermoplastic polyester elastomer TPEE, the modified filler, aluminum diethyl hypophosphite, an antioxidant and zinc stearate, adding the raw materials into an internal mixer, mixing for 10 minutes at the mixing temperature of 230 DEG C, extruding and granulating at the temperature of 200 DEG C after mixing is completed, carrying out mold pressing on granules for 5 minutes under the conditions of the temperature of 200 DEG C and the pressure of 10 MPa, and carrying out pressure maintaining and cooling to normal temperature, so as to obtain the wire harness protective sleeve material. The wire harness protective sleeve material prepared by the method has good heat resistance and mechanical strength, and can play a good role in protecting automobile wire harnesses in occasions with high temperature and stress requirements, so that the durability of the automobile wire harnesses is improved, and the maintenance cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of automobile wiring harness materials, and in particular to a high-temperature resistant new energy automobile wiring harness and a preparation method thereof. Background Art

[0002] The automotive wiring harness is the main body of automotive signal transmission and plays a vital role in automotive design and use. The wiring harness is mainly composed of wires and cables, protective covers, metal contacts, connectors, and wrapping fixtures. The automotive wiring harness connects various electronic components on the car. It must not only be able to accurately transmit various signals, but also ensure the reliability of the connection circuit, and requires a certain degree of heat resistance and anti-aging ability. The comprehensive requirements for protective covers for automotive wiring harnesses are high heat resistance, good mechanical properties, soft texture, and moderate cost. Although the widely used polyolefin heat shrinkable materials are low in cost and easy to process and shape, they have poor mechanical properties and heat resistance, and it is difficult to meet specific requirements. Summary of the invention

[0003] To this end, the present invention provides a method for preparing a high temperature resistant new energy vehicle wiring harness, the steps comprising:

[0004] (1) preparing a composite aqueous solution of urea and cetylpyridinium bromide and a composite ethanol solution of tetraethyl orthosilicate and ethylenediamine in a reaction kettle; heating the composite aqueous solution of urea and cetylpyridinium bromide to 50±5° C. in a water bath and then adding the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine to the solution under stirring, continuing to stir for more than 30 minutes after the addition is completed, then sealing the reaction kettle, heating to 120±5° C. and maintaining the temperature for more than 3 hours, cooling naturally to room temperature after the insulation is completed, opening the reaction kettle, separating the solid and the liquid, washing the solid phase with ethanol for more than 3 times, then washing with deionized water for more than 3 times, and drying at 60° C. for more than 10 hours to obtain a filler powder;

[0005] (2) preparing an ethanol solution of 3-aminopropyltriethoxysilane, immersing the filler powder in the ethanol solution of 3-aminopropyltriethoxysilane, heating the solution in a water bath to 60±5°C, stirring at this temperature for more than 20 hours, then separating the solid from the liquid, washing the solid phase with ethanol for more than 3 times, drying at 60°C for more than 5 hours, and immersing the dried solid phase in ethanol again, stirring with ultrasonic waves for more than 1 hour to obtain a dispersion, and then adding methyl acrylate to the dispersion under stirring. After the addition is completed, heating the solution in a water bath to 50±5°C, stirring at this temperature for more than 24 hours at 50±5°C in a nitrogen atmosphere, then separating the solid from the liquid, washing the solid phase with ethanol for more than 3 times, and drying at 60°C for more than 5 hours to obtain a treated filler;

[0006] (3) γ-methacryloxypropyltrimethoxysilane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide and the once treated filler are mixed in a reaction kettle, the mixture is heated to 60±5° C. and stirred at a constant temperature for more than 5 hours, then the reaction kettle is sealed, carbon dioxide gas is filled into it, and magnetic stirring is performed at a constant temperature of 60±5° C. and a pressure of 10 to 12 MPa for more than 4 hours, then the reaction kettle is opened, anhydrous ethanol is added, and stirring is performed for more than 20 minutes, and after solid-liquid separation, the solid phase is washed with ethanol for more than 2 times, and then washed with deionized water for more than 2 times, and dried at 60° C. for more than 5 hours to obtain a modified filler;

[0007] (4) Weigh the vacuum-dried thermoplastic polyester elastomer TPEE, the modified filler, diethyl aluminum hypophosphite, an antioxidant and zinc stearate, add the raw materials into an internal mixer and mix for 10 to 15 minutes at a mixing temperature of 230° C. After mixing, extrude and granulate at 200° C. The granules are molded at 200° C. and 10 MPa for 5 minutes, and then cooled to room temperature while maintaining pressure to obtain a wiring harness protective cover, and the wiring harness protective cover is wrapped around the outside of the automobile wiring harness to obtain the high-temperature resistant new energy automobile wiring harness.

[0008] Furthermore, in the step (1), in the composite aqueous solution of urea and cetylpyridinium bromide, the concentration of urea is 1.2-1.6 g / 100 mL, the concentration of cetylpyridinium bromide is 2.6-2.8 g / 100 mL, and the solvent is water; in the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine, the concentration of tetraethyl orthosilicate is 7-8 g / 100 mL, the concentration of ethylenediamine is 3-5 g / 100 mL, and the solvent is ethanol; the volume ratio of the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine added to the composite aqueous solution of urea and cetylpyridinium bromide is composite aqueous solution of urea and cetylpyridinium bromide: composite ethanol solution of tetraethyl orthosilicate and ethylenediamine = 1:1.

[0009] Furthermore, in the step (2), the concentration of 3-aminopropyltriethoxysilane in the ethanol solution of 3-aminopropyltriethoxysilane is 0.7-0.8 g / 100 mL, the solvent is ethanol, and the mass ratio of the filler powder immersed in the ethanol solution of 3-aminopropyltriethoxysilane is filler powder: ethanol solution of 3-aminopropyltriethoxysilane = 1:50-100.

[0010] Furthermore, in the step (2), the mass ratio of the dried solid phase immersed in ethanol again is the dried solid phase: ethanol = 1:50-60; the mass ratio of the added methyl acrylate to the dried solid phase added to prepare the dispersion is methyl acrylate: dried solid phase = 3-4:1.

[0011] Furthermore, in the step (3), the mass ratio of γ-methacryloxypropyltrimethoxysilane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide and the once-treated filler is γ-methacryloxypropyltrimethoxysilane: 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide: once-treated filler = 10:7 to 9:18 to 20; the mass ratio of the added anhydrous ethanol to the once-treated filler added to the reactor is anhydrous ethanol: once-treated filler = 50 to 200:1.

[0012] Furthermore, in the step (4), the raw materials are calculated by weight as follows: 100 parts of thermoplastic polyester elastomer TPEE, 3 to 5 parts of modified filler, 7 to 10 parts of diethyl aluminum hypophosphite, 1 to 2 parts of antioxidant, and 1 to 2 parts of zinc stearate.

[0013] The beneficial effects of the present invention are as follows: the wiring harness protective cover material prepared by the method of the present invention has good heat resistance and mechanical strength, and can also provide good protection for automobile wiring harnesses in situations where temperature and stress requirements are high, thereby improving the durability of automobile wiring harnesses and reducing maintenance costs. By comparing Example 3 of the present invention with the comparative examples, it can be seen that by adding the modified filler of the present invention to the thermoplastic polyester elastomer TPEE matrix material, the strength and heat resistance of the thermoplastic polyester elastomer TPEE can be significantly improved. The main reason for this is that: the present invention first synthesizes dendritic mesoporous silicon oxide particles, so that the particles are evenly distributed in the thermoplastic polyester elastomer TPEE matrix as a reinforcing phase, thereby improving the strength of the material; then, 3-aminopropyltriethoxysilane is used to form amino groups on the surface of the particles, and methyl acrylate is used for modification, thereby reducing the agglomeration of the particles and improving the The wettability of the particles with the thermoplastic polyester elastomer TPEE matrix reduces the amount of defects between the two phases; finally, phosphorus-containing groups are grafted on the surface of the particles through 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide. The phosphorus-containing groups can react with the polar functional groups of the thermoplastic polyester elastomer TPEE matrix to form connecting bonds such as phosphorus-oxygen bonds and phosphorus-nitrogen bonds, further improving the connection between the modified filler and the thermoplastic polyester elastomer TPEE matrix material, thereby improving the bonding strength of the two-phase interface and enhancing the overall mechanical strength and heat resistance of the material. DETAILED DESCRIPTION

[0014] The present invention will be further described below in conjunction with the embodiments.

[0015] Example 1

[0016] A method for preparing a high temperature resistant new energy vehicle wiring harness protective cover material, comprising:

[0017] (1) a composite aqueous solution of urea and cetylpyridinium bromide is prepared in a reaction kettle, wherein the concentration of urea in the composite aqueous solution of urea and cetylpyridinium bromide is 1.2 g / 100 mL, the concentration of cetylpyridinium bromide is 2.6 g / 100 mL, and the solvent is water; a composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is prepared, wherein the concentration of tetraethyl orthosilicate in the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is 7 g / 100 mL, the concentration of ethylenediamine is 3 g / 100 mL, and the solvent is ethanol; the composite aqueous solution of urea and cetylpyridinium bromide is heated in a water bath to 50° C. and then stirred. The composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is added to the solution in a state, and the volume ratio of the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is added to the composite aqueous solution of urea and cetylpyridinium bromide: the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is 1:1; after the addition is completed, stirring is continued for 30 minutes, and then the reactor is sealed, heated to 120° C. and kept warm for 3 hours, and naturally cooled to room temperature after the insulation is completed, the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed 3 times with ethanol, and then washed 3 times with deionized water, and dried at 60° C. for 10 hours to obtain filler powder;

[0018] (2) preparing an ethanol solution of 3-aminopropyl triethoxysilane, wherein the concentration of 3-aminopropyl triethoxysilane in the ethanol solution is 0.7 g / 100 mL and the solvent is ethanol, soaking the filler powder in the ethanol solution of 3-aminopropyl triethoxysilane, wherein the mass ratio of the filler powder to the ethanol solution of 3-aminopropyl triethoxysilane is filler powder: ethanol solution of 3-aminopropyl triethoxysilane = 1:50; heating in a water bath to 60° C., stirring at this temperature for 20 h, then separating the solid and the liquid, washing the solid phase with ethanol for 3 times, and rinsing at 60° C. Drying for 5 hours, the dried solid phase is immersed in ethanol again, and the mass ratio of the dried solid phase immersed in ethanol again is the dried solid phase: ethanol = 1:50; stirring for 1 hour under an ultrasonic environment to obtain a dispersion, and then adding methyl acrylate to the dispersion under stirring, the mass ratio of the added methyl acrylate to the dried solid phase added to prepare the dispersion is methyl acrylate: dried solid phase = 3:1; after the addition is completed, heating to 50°C in a water bath for insulation, stirring at a constant temperature of 50°C in a nitrogen atmosphere for 24 hours, then separating the solid and the liquid, washing the solid phase with ethanol 3 times, and drying at 60°C for 5 hours to obtain a treated filler;

[0019] (3) mixing γ-methacryloxypropyl trimethoxysilane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide and the once-treated filler in a reaction kettle, wherein the mass ratio of γ-methacryloxypropyl trimethoxysilane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide and the once-treated filler is γ-methacryloxypropyl trimethoxysilane: 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide: 0-oxide: once-treated filler = 10:7:18; the mixture is heated to 60°C and stirred at a constant temperature for 5 hours, then the reactor is sealed, filled with carbon dioxide gas, and magnetically stirred at 60°C and 10MPa pressure for 4 hours, then the reactor is opened, anhydrous ethanol is added, and the mass ratio of the anhydrous ethanol added to the once-treated filler added to the reactor is anhydrous ethanol: once-treated filler = 50:1; stirred for 20 minutes, solid-liquid separation, the solid phase is washed twice with ethanol, and then washed twice with deionized water, and dried at 60°C for 5 hours to obtain a modified filler;

[0020] (4) Weigh the vacuum-dried thermoplastic polyester elastomer TPEE, the modified filler, diethyl aluminum hypophosphite, an antioxidant and zinc stearate, wherein the weight proportion of each raw material is as follows: 100 parts of thermoplastic polyester elastomer TPEE, 3 parts of modified filler, 7 parts of diethyl aluminum hypophosphite, 1 part of antioxidant and 1 part of zinc stearate; add each raw material into an internal mixer and mix for 10 minutes at a mixing temperature of 230° C. After mixing, extrude and granulate at 200° C., mold the granules at 200° C. and 10 MPa for 5 minutes to form a test specimen, and cool to room temperature while maintaining pressure to obtain a wire harness protective cover material.

[0021] Example 2

[0022] A method for preparing a high temperature resistant new energy vehicle wiring harness protective cover material, comprising:

[0023] (1) In a reaction kettle, a composite aqueous solution of urea and cetylpyridinium bromide is prepared, wherein the concentration of urea in the composite aqueous solution of urea and cetylpyridinium bromide is 1.4 g / 100 mL, the concentration of cetylpyridinium bromide is 2.7 g / 100 mL, and the solvent is water; a composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is prepared, wherein the concentration of tetraethyl orthosilicate in the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is 7 g / 100 mL, the concentration of ethylenediamine is 4 g / 100 mL, and the solvent is ethanol; the composite aqueous solution of urea and cetylpyridinium bromide is heated to 50° C. in a water bath and then stirred. The composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is added to the solution in a state, and the volume ratio of the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is added to the composite aqueous solution of urea and cetylpyridinium bromide: the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is 1:1; after the addition is completed, stirring is continued for 30 minutes, and then the reactor is sealed, heated to 120° C. and kept warm for 3 hours, and naturally cooled to room temperature after the insulation is completed, the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed 3 times with ethanol, and then washed 3 times with deionized water, and dried at 60° C. for 10 hours to obtain filler powder;

[0024] (2) preparing an ethanol solution of 3-aminopropyl triethoxysilane, wherein the concentration of 3-aminopropyl triethoxysilane in the ethanol solution is 0.7 g / 100 mL and the solvent is ethanol, soaking the filler powder in the ethanol solution of 3-aminopropyl triethoxysilane, wherein the mass ratio of the filler powder to the ethanol solution of 3-aminopropyl triethoxysilane is filler powder: ethanol solution of 3-aminopropyl triethoxysilane = 1:50; heating in a water bath to 60° C., stirring at this temperature for 20 h, then separating the solid and the liquid, washing the solid phase with ethanol for 3 times, and rinsing at 60° C. Drying for 5 hours, the dried solid phase is immersed in ethanol again, and the mass ratio of the dried solid phase immersed in ethanol again is the dried solid phase: ethanol = 1:50; stirring for 1 hour under an ultrasonic environment to obtain a dispersion, and then adding methyl acrylate to the dispersion under stirring, the mass ratio of the added methyl acrylate to the dried solid phase added to prepare the dispersion is methyl acrylate: dried solid phase = 3:1; after the addition is completed, heating to 50°C in a water bath for insulation, stirring at a constant temperature of 50°C in a nitrogen atmosphere for 24 hours, then separating the solid and the liquid, washing the solid phase with ethanol 3 times, and drying at 60°C for 5 hours to obtain a treated filler;

[0025] (3) mixing γ-methacryloxypropyl trimethoxysilane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide and the once-treated filler in a reaction kettle, wherein the mass ratio of γ-methacryloxypropyl trimethoxysilane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide and the once-treated filler is γ-methacryloxypropyl trimethoxysilane: 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide: 0-oxide: once-treated filler = 10:8:19; the mixture is heated to 60°C and stirred at a constant temperature for 5 hours, then the reactor is sealed, filled with carbon dioxide gas, and magnetically stirred at 60°C and 10MPa pressure for 4 hours, then the reactor is opened, anhydrous ethanol is added, and the mass ratio of the anhydrous ethanol added to the once-treated filler added to the reactor is anhydrous ethanol: once-treated filler = 50:1; stirred for 20 minutes, solid-liquid separation, the solid phase is washed twice with ethanol, and then washed twice with deionized water, and dried at 60°C for 5 hours to obtain a modified filler;

[0026] (4) Weigh the vacuum-dried thermoplastic polyester elastomer TPEE, the modified filler, diethyl aluminum hypophosphite, an antioxidant and zinc stearate, wherein the weight proportion of each raw material is as follows: 100 parts of thermoplastic polyester elastomer TPEE, 4 parts of modified filler, 8 parts of diethyl aluminum hypophosphite, 1 part of antioxidant and 1 part of zinc stearate; add each raw material into an internal mixer and mix for 10 minutes at a mixing temperature of 230° C. After mixing, granulate is extruded at 200° C., and the granules are molded at 200° C. and 10 MPa for 5 minutes to form a test specimen, and then cooled to room temperature while maintaining pressure to obtain a wire harness protective cover material.

[0027] Example 3

[0028] A method for preparing a high temperature resistant new energy vehicle wiring harness protective cover material, comprising:

[0029] (1) a composite aqueous solution of urea and cetylpyridinium bromide is prepared in a reaction kettle, wherein the concentration of urea in the composite aqueous solution of urea and cetylpyridinium bromide is 1.4 g / 100 mL, the concentration of cetylpyridinium bromide is 2.7 g / 100 mL, and the solvent is water; a composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is prepared, wherein the concentration of tetraethyl orthosilicate in the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is 8 g / 100 mL, the concentration of ethylenediamine is 4 g / 100 mL, and the solvent is ethanol; the composite aqueous solution of urea and cetylpyridinium bromide is heated in a water bath to 50° C. and then stirred. The composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is added to the solution in a state, and the volume ratio of the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is added to the composite aqueous solution of urea and cetylpyridinium bromide: the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is 1:1; after the addition is completed, stirring is continued for 30 minutes, and then the reactor is sealed, heated to 120° C. and kept warm for 3 hours, and naturally cooled to room temperature after the insulation is completed, the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed 3 times with ethanol, and then washed 3 times with deionized water, and dried at 60° C. for 10 hours to obtain filler powder;

[0030] (2) preparing an ethanol solution of 3-aminopropyl triethoxysilane, wherein the concentration of 3-aminopropyl triethoxysilane in the ethanol solution is 0.8 g / 100 mL and the solvent is ethanol, soaking the filler powder in the ethanol solution of 3-aminopropyl triethoxysilane, wherein the mass ratio of the filler powder to the ethanol solution of 3-aminopropyl triethoxysilane is filler powder: ethanol solution of 3-aminopropyl triethoxysilane = 1:50; heating in a water bath to 60° C., stirring at this temperature for 20 h, then separating the solid from the liquid, washing the solid phase with ethanol for 3 times, and rinsing at 60° C. Drying for 5 hours, the dried solid phase is immersed in ethanol again, and the mass ratio of the dried solid phase immersed in ethanol again is the dried solid phase: ethanol = 1:50; stirring for 1 hour under an ultrasonic environment to obtain a dispersion, and then adding methyl acrylate to the dispersion under stirring, the mass ratio of the added methyl acrylate to the dried solid phase added to prepare the dispersion is methyl acrylate: dried solid phase = 4:1; after the addition is completed, heating to 50°C in a water bath for insulation, stirring at a constant temperature of 50°C in a nitrogen atmosphere for 24 hours, then solid-liquid separation, the solid phase is washed 3 times with ethanol, and dried at 60°C for 5 hours to obtain a treated filler;

[0031] (3) mixing γ-methacryloxypropyl trimethoxysilane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide and the once-treated filler in a reaction kettle, wherein the mass ratio of γ-methacryloxypropyl trimethoxysilane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide and the once-treated filler is γ-methacryloxypropyl trimethoxysilane: 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide: 0-oxide: once-treated filler = 10:8:19; the mixture is heated to 60°C and stirred at a constant temperature for 5 hours, then the reactor is sealed, filled with carbon dioxide gas, and magnetically stirred at 60°C and 10MPa pressure for 4 hours, then the reactor is opened, anhydrous ethanol is added, and the mass ratio of the anhydrous ethanol added to the once-treated filler added to the reactor is anhydrous ethanol: once-treated filler = 50:1; stirred for 20 minutes, solid-liquid separation, the solid phase is washed twice with ethanol, and then washed twice with deionized water, and dried at 60°C for 5 hours to obtain a modified filler;

[0032] (4) Weigh the vacuum-dried thermoplastic polyester elastomer TPEE, the modified filler, diethyl aluminum hypophosphite, an antioxidant and zinc stearate, wherein the weight proportion of each raw material is as follows: 100 parts of thermoplastic polyester elastomer TPEE, 4 parts of modified filler, 9 parts of diethyl aluminum hypophosphite, 2 parts of antioxidant and 2 parts of zinc stearate; add each raw material into an internal mixer and mix for 10 minutes at a mixing temperature of 230° C. After mixing, granulate is extruded at 200° C., and the granules are molded at 200° C. and 10 MPa for 5 minutes to form a test specimen, and then cooled to room temperature while maintaining pressure to obtain a wire harness protective cover material.

[0033] Example 4

[0034] A method for preparing a high temperature resistant new energy vehicle wiring harness protective cover material, comprising:

[0035] (1) a composite aqueous solution of urea and cetylpyridinium bromide is prepared in a reaction kettle, wherein the concentration of urea in the composite aqueous solution of urea and cetylpyridinium bromide is 1.6 g / 100 mL, the concentration of cetylpyridinium bromide is 2.8 g / 100 mL, and the solvent is water; a composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is prepared, wherein the concentration of tetraethyl orthosilicate in the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is 8 g / 100 mL, the concentration of ethylenediamine is 5 g / 100 mL, and the solvent is ethanol; the composite aqueous solution of urea and cetylpyridinium bromide is heated to 50° C. in a water bath and then stirred. The composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is added to the solution in a state, and the volume ratio of the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is added to the composite aqueous solution of urea and cetylpyridinium bromide: the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is 1:1; after the addition is completed, stirring is continued for 30 minutes, and then the reactor is sealed, heated to 120° C. and kept warm for 3 hours, and naturally cooled to room temperature after the insulation is completed, the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed 3 times with ethanol, and then washed 3 times with deionized water, and dried at 60° C. for 10 hours to obtain filler powder;

[0036] (2) preparing an ethanol solution of 3-aminopropyl triethoxysilane, wherein the concentration of 3-aminopropyl triethoxysilane in the ethanol solution is 0.8 g / 100 mL and the solvent is ethanol, soaking the filler powder in the ethanol solution of 3-aminopropyl triethoxysilane, wherein the mass ratio of the filler powder to the ethanol solution of 3-aminopropyl triethoxysilane is filler powder: ethanol solution of 3-aminopropyl triethoxysilane = 1:50; heating in a water bath to 60° C., stirring at this temperature for 20 h, then separating the solid from the liquid, washing the solid phase with ethanol for 3 times, and rinsing at 60° C. Drying for 5 hours, the dried solid phase is immersed in ethanol again, and the mass ratio of the dried solid phase immersed in ethanol again is the dried solid phase: ethanol = 1:50; stirring for 1 hour under an ultrasonic environment to obtain a dispersion, and then adding methyl acrylate to the dispersion under stirring, the mass ratio of the added methyl acrylate to the dried solid phase added to prepare the dispersion is methyl acrylate: dried solid phase = 4:1; after the addition is completed, heating to 50°C in a water bath for insulation, stirring at a constant temperature of 50°C in a nitrogen atmosphere for 24 hours, then solid-liquid separation, the solid phase is washed 3 times with ethanol, and dried at 60°C for 5 hours to obtain a treated filler;

[0037] (3) mixing γ-methacryloxypropyl trimethoxysilane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide and the once-treated filler in a reaction kettle, wherein the mass ratio of γ-methacryloxypropyl trimethoxysilane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide and the once-treated filler is γ-methacryloxypropyl trimethoxysilane: 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide: 0-oxide: once-treated filler = 10:9:20; the mixture is heated to 60°C and stirred at a constant temperature for 5 hours, then the reactor is sealed, filled with carbon dioxide gas, and magnetically stirred at 60°C and 10MPa pressure for 4 hours, then the reactor is opened, anhydrous ethanol is added, and the mass ratio of the anhydrous ethanol added to the once-treated filler added to the reactor is anhydrous ethanol: once-treated filler = 50:1; stirred for 20 minutes, solid-liquid separation, the solid phase is washed twice with ethanol, and then washed twice with deionized water, and dried at 60°C for 5 hours to obtain a modified filler;

[0038] (4) Weigh the vacuum-dried thermoplastic polyester elastomer TPEE, the modified filler, diethyl aluminum hypophosphite, an antioxidant and zinc stearate, wherein the weight proportion of each raw material is as follows: 100 parts of thermoplastic polyester elastomer TPEE, 5 parts of modified filler, 10 parts of diethyl aluminum hypophosphite, 2 parts of antioxidant and 2 parts of zinc stearate; add each raw material into an internal mixer and mix for 10 minutes at a mixing temperature of 230° C. After mixing, extrude and granulate at 200° C., mold the granules at 200° C. and 10 MPa for 5 minutes to form a test specimen, and cool to room temperature while maintaining pressure to obtain a wire harness protective cover material.

[0039] Comparative Example 1

[0040] A method for preparing a wire harness protective cover material as a comparison, the steps comprising:

[0041] (1) a composite aqueous solution of urea and cetylpyridinium bromide is prepared in a reaction kettle, wherein the concentration of urea in the composite aqueous solution of urea and cetylpyridinium bromide is 1.4 g / 100 mL, the concentration of cetylpyridinium bromide is 2.7 g / 100 mL, and the solvent is water; a composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is prepared, wherein the concentration of tetraethyl orthosilicate in the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is 8 g / 100 mL, the concentration of ethylenediamine is 4 g / 100 mL, and the solvent is ethanol; the composite aqueous solution of urea and cetylpyridinium bromide is heated in a water bath to 50° C. and then stirred. The composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is added to the solution in a state, and the volume ratio of the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is added to the composite aqueous solution of urea and cetylpyridinium bromide: the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is 1:1; after the addition is completed, stirring is continued for 30 minutes, and then the reactor is sealed, heated to 120° C. and kept warm for 3 hours, and naturally cooled to room temperature after the insulation is completed, the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed 3 times with ethanol, and then washed 3 times with deionized water, and dried at 60° C. for 10 hours to obtain filler powder;

[0042] (2) preparing an ethanol solution of 3-aminopropyltriethoxysilane, wherein the concentration of 3-aminopropyltriethoxysilane in the ethanol solution is 0.8 g / 100 mL, and the solvent is ethanol; immersing the filler powder in the ethanol solution of 3-aminopropyltriethoxysilane; the mass ratio of the filler powder to the ethanol solution of 3-aminopropyltriethoxysilane is filler powder: ethanol solution of 3-aminopropyltriethoxysilane = 1:50; heating in a water bath to 60° C., stirring at this temperature for 20 h, then separating the solid from the liquid, washing the solid phase with ethanol three times, and drying at 60° C. for 5 h to obtain the once-treated filler of this comparative example;

[0043] (3) mixing γ-methacryloxypropyl trimethoxysilane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide and the once-treated filler in a reaction kettle, wherein the mass ratio of γ-methacryloxypropyl trimethoxysilane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide and the once-treated filler is γ-methacryloxypropyl trimethoxysilane: 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide: 0-oxide: once-treated filler = 10:8:19; the mixture is heated to 60°C and stirred at a constant temperature for 5 hours, then the reactor is sealed, filled with carbon dioxide gas, and magnetically stirred at 60°C and 10MPa pressure for 4 hours, then the reactor is opened, anhydrous ethanol is added, and the mass ratio of the anhydrous ethanol added to the once-treated filler added to the reactor is anhydrous ethanol: once-treated filler = 50:1; stirred for 20 minutes, solid-liquid separation, the solid phase is washed twice with ethanol, and then washed twice with deionized water, and dried at 60°C for 5 hours to obtain a modified filler;

[0044] (4) Weigh the vacuum-dried thermoplastic polyester elastomer TPEE, the modified filler, diethyl aluminum hypophosphite, an antioxidant and zinc stearate, wherein the weight proportion of each raw material is as follows: 100 parts of thermoplastic polyester elastomer TPEE, 4 parts of modified filler, 9 parts of diethyl aluminum hypophosphite, 2 parts of antioxidant and 2 parts of zinc stearate; add each raw material into an internal mixer and mix for 10 minutes at a mixing temperature of 230° C. After mixing, granulate is extruded at 200° C., and the granules are molded at 200° C. and 10 MPa for 5 minutes to form a test specimen, and then cooled to room temperature while maintaining pressure to obtain the wiring harness protective cover material of this comparative example.

[0045] Comparative Example 2

[0046] A method for preparing a wire harness protective cover material as a comparison, the steps comprising:

[0047] (1) a composite aqueous solution of urea and cetylpyridinium bromide is prepared in a reaction kettle, wherein the concentration of urea in the composite aqueous solution of urea and cetylpyridinium bromide is 1.4 g / 100 mL, the concentration of cetylpyridinium bromide is 2.7 g / 100 mL, and the solvent is water; a composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is prepared, wherein the concentration of tetraethyl orthosilicate in the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is 8 g / 100 mL, the concentration of ethylenediamine is 4 g / 100 mL, and the solvent is ethanol; the composite aqueous solution of urea and cetylpyridinium bromide is heated in a water bath to 50° C. and then stirred. The composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is added to the solution in a state, and the volume ratio of the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is added to the composite aqueous solution of urea and cetylpyridinium bromide: the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine is 1:1; after the addition is completed, stirring is continued for 30 minutes, and then the reactor is sealed, heated to 120° C. and kept warm for 3 hours, and naturally cooled to room temperature after the insulation is completed, the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed 3 times with ethanol, and then washed 3 times with deionized water, and dried at 60° C. for 10 hours to obtain filler powder;

[0048] (2) preparing an ethanol solution of 3-aminopropyl triethoxysilane, wherein the concentration of 3-aminopropyl triethoxysilane in the ethanol solution is 0.8 g / 100 mL and the solvent is ethanol, soaking the filler powder in the ethanol solution of 3-aminopropyl triethoxysilane, wherein the mass ratio of the filler powder to the ethanol solution of 3-aminopropyl triethoxysilane is filler powder: ethanol solution of 3-aminopropyl triethoxysilane = 1:50; heating in a water bath to 60° C., stirring at this temperature for 20 h, then separating the solid from the liquid, washing the solid phase with ethanol for 3 times, and drying at 60° C. 5h, the dried solid phase was immersed in ethanol again, and the mass ratio of the dried solid phase immersed in ethanol again was the dried solid phase: ethanol = 1:50; stirred for 1h under ultrasonic environment to obtain a dispersion, and then methyl acrylate was added to the dispersion under stirring, and the mass ratio of the added mass of the methyl acrylate to the dried solid phase added to prepare the dispersion was methyl acrylate: dried solid phase = 4:1; after the addition was completed, it was heated to 50°C in a water bath for insulation, stirred at a constant temperature of 50°C in a nitrogen atmosphere for 24h, and then the solid-liquid was separated, the solid phase was washed 3 times with ethanol, and dried at 60°C for 5h to obtain the modified filler of this comparative example;

[0049] (3) Weigh the vacuum-dried thermoplastic polyester elastomer TPEE, the modified filler, diethyl aluminum hypophosphite, an antioxidant and zinc stearate, wherein the weight proportion of each raw material is as follows: 100 parts of thermoplastic polyester elastomer TPEE, 4 parts of modified filler, 9 parts of diethyl aluminum hypophosphite, 2 parts of antioxidant and 2 parts of zinc stearate; add each raw material into an internal mixer and mix for 10 minutes at a mixing temperature of 230° C. After mixing, granulate is extruded at 200° C., and the granules are molded at 200° C. and 10 MPa for 5 minutes to form a test specimen, and then cooled to room temperature while maintaining pressure to obtain the wiring harness protective cover material of this comparative example.

[0050] Example 5

[0051] The tensile properties of the test specimens prepared by the methods described in the above embodiments and comparative examples were tested according to the requirements of standard ASTM D412. The tensile speed was set to 100 mm / min. Three samples were tested for each group of samples, and the average value was taken as the tensile strength of the group. The test specimens prepared by the methods described in the above embodiments and comparative examples were kept at 180° C. for 200 h, and then the surface was observed for cracks. The results are shown in Table 1.

[0052] As can be seen from Table 1, the wiring harness protective cover material prepared by the method of the present invention has good heat resistance and mechanical strength, and can also provide good protection for automobile wiring harnesses in situations where temperature and stress requirements are high, thereby improving the durability of automobile wiring harnesses and reducing maintenance costs. By comparing Example 3 of the present invention and the comparative examples, it can be seen that by adding the modified filler of the present invention to the thermoplastic polyester elastomer TPEE matrix material, the strength and heat resistance of the thermoplastic polyester elastomer TPEE can be significantly improved. The main reason is that: the present invention first synthesizes dendritic mesoporous silicon oxide particles, so that the particles are evenly distributed in the thermoplastic polyester elastomer TPEE matrix as a reinforcing phase, thereby improving the strength of the material; then, 3-aminopropyltriethoxysilane is used to form amino groups on the surface of the particles, and methyl acrylate is used for modification, thereby reducing the agglomeration of the particles and improving the The wettability of the particles with the thermoplastic polyester elastomer TPEE matrix reduces the amount of defects between the two phases; finally, phosphorus-containing groups are grafted on the surface of the particles through 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide. The phosphorus-containing groups can react with the polar functional groups of the thermoplastic polyester elastomer TPEE matrix to form connecting bonds such as phosphorus-oxygen bonds and phosphorus-nitrogen bonds, further improving the connection between the modified filler and the thermoplastic polyester elastomer TPEE matrix material, thereby improving the bonding strength of the two-phase interface and enhancing the overall mechanical strength and heat resistance of the material.

[0053] Table 1

[0054] Experimental Group Tensile strength(MPa) 180℃ insulation for 200h Example 1 23.06 No cracks on the surface Example 2 24.72 No cracks on the surface Example 3 24.95 No cracks on the surface Example 4 24.20 No cracks on the surface Comparative Example 1 19.14 Surface cracks Comparative Example 2 18.87 Surface cracks

[0055] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A method for preparing a high temperature resistant new energy vehicle wiring harness, characterized in that the steps include: (1) preparing a composite aqueous solution of urea and cetylpyridinium bromide and a composite ethanol solution of tetraethyl orthosilicate and ethylenediamine in a reaction kettle; heating the composite aqueous solution of urea and cetylpyridinium bromide to 50±5° C. in a water bath and then adding the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine to the solution under stirring, continuing to stir for more than 30 minutes after the addition is completed, then sealing the reaction kettle, heating to 120±5° C. and maintaining the temperature for more than 3 hours, cooling naturally to room temperature after the insulation is completed, opening the reaction kettle, separating the solid and the liquid, washing the solid phase with ethanol for more than 3 times, then washing with deionized water for more than 3 times, and drying at 60° C. for more than 10 hours to obtain a filler powder; (2) preparing an ethanol solution of 3-aminopropyltriethoxysilane, immersing the filler powder in the ethanol solution of 3-aminopropyltriethoxysilane, heating the solution in a water bath to 60±5°C, stirring at this temperature for more than 20 hours, then separating the solid from the liquid, washing the solid phase with ethanol for more than 3 times, drying at 60°C for more than 5 hours, and immersing the dried solid phase in ethanol again, stirring with ultrasonic waves for more than 1 hour to obtain a dispersion, and then adding methyl acrylate to the dispersion under stirring. After the addition is completed, heating the solution in a water bath to 50±5°C, stirring at this temperature for more than 24 hours at 50±5°C in a nitrogen atmosphere, then separating the solid from the liquid, washing the solid phase with ethanol for more than 3 times, and drying at 60°C for more than 5 hours to obtain a treated filler; (3) γ-methacryloxypropyltrimethoxysilane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide and the once treated filler are mixed in a reaction kettle, the mixture is heated to 60±5° C. and stirred at a constant temperature for more than 5 hours, then the reaction kettle is sealed, carbon dioxide gas is filled into it, and magnetic stirring is performed at a constant temperature of 60±5° C. and a pressure of 10 to 12 MPa for more than 4 hours, then the reaction kettle is opened, anhydrous ethanol is added, and stirring is performed for more than 20 minutes, and after solid-liquid separation, the solid phase is washed with ethanol for more than 2 times, and then washed with deionized water for more than 2 times, and dried at 60° C. for more than 5 hours to obtain a modified filler; (4) Weigh the vacuum-dried thermoplastic polyester elastomer TPEE, the modified filler, diethyl aluminum hypophosphite, an antioxidant and zinc stearate, add the raw materials into an internal mixer and mix for 10 to 15 minutes at a mixing temperature of 230° C. After mixing, extrude and granulate at 200° C. The granules are molded at 200° C. and 10 MPa for 5 minutes, and then cooled to room temperature while maintaining pressure to obtain a wiring harness protective cover, and the wiring harness protective cover is wrapped around the outside of the automobile wiring harness to obtain the high-temperature resistant new energy automobile wiring harness.

2. The method for preparing a high temperature resistant new energy vehicle wiring harness according to claim 1, characterized in that: In the step (1), in the composite aqueous solution of urea and cetylpyridinium bromide, the concentration of urea is 1.2-1.6 g / 100 mL, the concentration of cetylpyridinium bromide is 2.6-2.8 g / 100 mL, and the solvent is water; in the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine, the concentration of tetraethyl orthosilicate is 7-8 g / 100 mL, the concentration of ethylenediamine is 3-5 g / 100 mL, and the solvent is ethanol; the volume ratio of the composite ethanol solution of tetraethyl orthosilicate and ethylenediamine added to the composite aqueous solution of urea and cetylpyridinium bromide is urea / cetylpyridinium bromide composite aqueous solution: composite ethanol solution of tetraethyl orthosilicate and ethylenediamine = 1:

1.

3. The method for preparing a high temperature resistant new energy vehicle wiring harness according to claim 1, characterized in that: In the step (2), the concentration of 3-aminopropyltriethoxysilane in the ethanol solution of 3-aminopropyltriethoxysilane is 0.7-0.8 g / 100 mL, the solvent is ethanol, and the mass ratio of the filler powder immersed in the ethanol solution of 3-aminopropyltriethoxysilane is filler powder: ethanol solution of 3-aminopropyltriethoxysilane = 1:50-100.

4. The method for preparing a high temperature resistant new energy vehicle wiring harness according to claim 1, characterized in that: In the step (2), the mass ratio of the dried solid phase immersed in ethanol again is dried solid phase: ethanol = 1:50-60; the mass ratio of the added methyl acrylate to the dried solid phase added to prepare the dispersion is methyl acrylate: dried solid phase = 3-4:

1.

5. The method for preparing a high temperature resistant new energy vehicle wiring harness according to claim 1, characterized in that: In the step (3), the mass ratio of γ-methacryloxypropyltrimethoxysilane, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide and the once-treated filler is γ-methacryloxypropyltrimethoxysilane: 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-propionic acid methyl ester 10-oxide: once-treated filler = 10:7 to 9:18 to 20; the mass ratio of the added anhydrous ethanol to the once-treated filler added to the reactor is anhydrous ethanol: once-treated filler = 50 to 200:

1.

6. The method for preparing a high temperature resistant new energy vehicle wiring harness according to claim 1, characterized in that: In the step (4), the raw materials are calculated by weight as follows: 100 parts of thermoplastic polyester elastomer TPEE, 3 to 5 parts of modified filler, 7 to 10 parts of diethyl aluminum hypophosphite, 1 to 2 parts of antioxidant, and 1 to 2 parts of zinc stearate.

Citation Information

Patent Citations

  • TPEE (thermoplastic polyether ester elastomer) composite as well as preparation method and application thereof

    CN110041663A

  • Halogen-free flame-retardant polyether ester elastomer composition and preparation method thereof

    CN112457635A

  • Flame Retardant Thermoplastic Elastomer Composition with Resistance to Scratch-Whitening

    US20130030093A1

  • Copolyester elastomer and an alpha-olefin vinyl acetate copolymer having flame retardant properties

    US20150218365A1

Cited By

  • 125 DEG C irradiation crosslinking elastomer automobile wire harness material for new energy automobile and preparation method of 125 DEG C irradiation crosslinking elastomer automobile wire harness material

    CN121495238A